Construction of innovative 3D-weaved carbon mesh anode network to boost electron transfer and microbial activity in bioelectrochemical system. (1st April 2020) - Luo, Shuai; Fu, Boya; Liu, Fubin; He, Kai; Yang, Heng; Ma, Junjun; Wang, Han; Zhang, Xiaoyuan; Liang, Peng; Huang, Xia
Abstract: Bioelectrochemical system (BES) is promising technology to simultaneously treat wastewater and recover energy, and electrode material is important for the system performance. Microbial fuel cell (MFC) is one of typical BES to be applied in wastewater treatment. How to improve the electrode material is significant to improve wastewater treatment, energy recovery and cost effectiveness. In this study, 3D-weaved carbon electrode entity, assembled by multiple pieces of carbon mesh (CM), was proposed to combine all electrode components as entity to facilitate electron conduction and ionic migration, compared with carbon brush (CB) and granular activated carbon (GAC). The result showed that current density and internal resistance of MFC using 3D-weaved CM as horizontally extended inside anode (CM(T)) were 30.9 A m-3 and 4.5 Ω, respectively, with higher output than traditional GAC (22.6 A m-3 and 6.2 Ω). Though GAC had greater electrode filling and surface area for biomass growth, the electron transfer efficiency per unit electrode biomass was only at 0.0019 ± 0.0002 mol g-1 d-1, much lower than CM(T) at 0.0077 ± 0.0009 mol g-1 day-1. Higher ionic migration rate of CM(T) suggested the assisting effect of composite electrode to enhance ionic transportation towards the cathode. Microbial analysis further indicated that 3D-CM electrode network could simultaneously enhance Geobacter abundance and methanogen activity, suggesting the importance of electrode network on electricigens. Furthermore, CM(T) could obtain 10 times higher energy output efficiency than traditional GAC when applied inside anode chamber. This study proved that network construction of anode electrode could promote the electrode performance and cost effectiveness, suggesting the future development of reactor design of bioelectrochemical system. Graphical abstract: Image 1 Highlights: Anode configuration impacted biomass growth and electron conduction. 3D carbon mesh constructed as electron network entity for conducting facility. Electrode entity construction greatly benefited electron generation efficiency. 3D carbon mesh stimulated microbial activity and Geobacter growth. Massive cost optimization achieved by 3D carbon mesh.